SYNTHESIS, CARACTERIZATION AND EVALUATION OF BIOLOGICAL ACTIVITY OF COBALT WITH PYRAZINAMIDE COORDINATION COMPOUNDS - Chávez Llallire, Natalia Karolina (2020)
In this study, two new cobalt with pyrazinamide (PZA) coordination compounds: Co-PZA (1) and Co-PZA (2) were synthesized from two cobalt precursor salts. The aim of this study is to elucidate the chemical structure of each synthesized complex by using characterization techniques, as well as to evaluate their anti-tuberculous activity compared to pyrazinamide. The characterization techniques comprised, C, H and N elemental analysis, atomic absorption spectroscopy of cobalt, thermogravimetric analysis, magnetic susceptibility, UV-Visible, infrared and Raman spectroscopy. The antibiotic activity was tested by determining the minimum inhibitory concentration in a Mycobacterium tuberculosis culture. The predicted molecular formulas from characterization results were: [Co(PZA)2Cl2] for Co-PZA (1) complex and [Co(PZA)2(NO3)2].H2O for Co-PZA (2) complex. The two complexes showed a higher antimicrobial capacity than pyrazinamide.